Interpetrosal sphingosine-1-phosphate ratio predicting Cushing’s disease tumor laterality and remission after surgery - Sun, Heng; Wu, Chunli; Hu, Biao; Xiao, Yuan (Frontiers in Endocrinology, 2023)
Background: Cushing's disease (CD) poses significant challenges in its treatment due to the lack of reliable biomarkers for predicting tumor localization or postoperative clinical outcomes. Sphingosine-1-phosphate (S1P) has been shown to increase cortisol biosynthesis and is regulated by adrenocorticotropic hormone (ACTH). Methods: We employed bilateral inferior petrosal sinus sampling (BIPSS), which is considered the gold standard for diagnosing pituitary sources of CD, to obtain blood samples and explore the clinical predictive value of the S1P concentration ratio in determining tumor laterality and postoperative remission. We evaluated 50 samples from 25 patients who underwent BIPSS to measure S1P levels in the inferior petrosal sinuses bilaterally. Results: Serum S1P levels in patients with CD were significantly higher on the adenoma side of the inferior petrosal sinus than on the nonadenoma side (397.7±15.4 vs. 261.9±14.88; P ˂ 0.05). The accuracy of diagnosing tumor laterality with the interpetrosal S1P and ACTH ratios and the combination of the two was 64%, 56% and 73%, respectively. The receiver operating characteristic curve analysis revealed that the combination of interpetrosal S1P and ACTH ratios, as a predictor of tumor laterality, exhibited a sensitivity of 81.82% and a specificity of 75%, with an area under the curve value of 84.09%. Moreover, we observed that a high interpetrosal S1P ratio was associated with nonremission after surgery. Correlation analyses demonstrated that the interpetrosal S1P ratio was associated with preoperative follicle-stimulating hormone (FSH) , luteinizing hormone (LH), and postoperative ACTH 8 am levels (P ˂ 0.05). Conclusion: Our study demonstrated a significant association between the interpetrosal S1P ratio and tumor laterality, as well as postoperative remission in CD, suggesting that the interpetrosal S1P ratio could serve as a valuable biomarker in clinical practice.